Knowledge of Clinical Frailty Scale among Intensive Care Nurses at Tertiary Care Hospital: Knowledge of Clinical Frailty Scale Among Intensive Care Nurses - Ramzan, Muhammad; Marshall, Pamela; Hashmi, Madiha (Pakistan Journal of Health Sciences, 2024)
Clinical Frailty Scale (CFS) is an easy way to measure, all elderly ICU patients on a regular basis, especially when advanced care plans are involved. It ought to be applied when making decisions for family members and nurses as well. Objective: To determine the knowledge of the clinical frailty scale among intensive care nurses at Tertiary Care Hospital. Method: The cross-sectional study was conducted at Tertiary Care Hospital of Karachi from 1st January to 15th March 2024. Data were collected by a valid and reliable tool through the convenience sampling technique from ICU nurses having minimum of three months of experience, was included. Other nurses who were on leave during data collection and nursing students were excluded from the study. Results: A total of 65 respondents participated in the study, majority 39 (60%) of them were from the age group 25 to 35 years. More than half 36 (55.4%) had a B.S. nursing qualification. Most of the respondents had ≤ 5 years of total clinical experience in 55 (84.6%), and ICU experience in 62 (95.4%). Out of total participants, 60 (92%) of the respondents had poor knowledge, followed by fair 5 (8%) knowledge while 0 (0%) participants had good knowledge about CFS. Conclusions: It was concluded that the knowledge of nurses regarding clinical frailty scale was poor. Knowing more about the knowledge of clinical frailty scale among ICU nurses who frequently care for frail and older patients can help identify frailty and multidisciplinary care. Educating nurses more about frailty may promote nursing care strategies for frail patients